Potencial biotecnológico de bactérias endofíticas e rizosféricas de Paspalum spp. e nanopartículas de sílica para promoção de crescimento vegetal - Moraes, Amanda Carolina Prado de (2021)
Bacteria associated with Paspalum plants can be employed as biofertilizers to increase the efficiency of pastures and reduce the use of agrochemicals by converting nutrients into an assimilable form for the host plant and defense against phytopathogens. In this context, silica nanoparticles (NPs) can be a tool to increase the effectiveness of biofertilizers in the field. This study aimed to isolate, identify and characterize the endophytic and rhizospheric microbiota of Paspalum spp. for plant growth promotion and to evaluate the effect of these bacterial isolates associated with silica NPs in Paspalum notatum seedlings. The bacteria were isolated from roots, leaves, and soils of P. rojasii, P. compressifolium, and P. lenticulare and tested in vitro for biological nitrogen fixation, phosphate solubilization, indole-3-acidic acid (IAA) production, and antagonism against the phytopathogenic fungi Claviceps purpurea and Fusarium oxysporum. The bacteria with biotechnological potential were identified by the 16S rDNA sequencing, and isolates of the genera Alcaligenes, Pseudomonas, Enterobacter, and Serratia were selected for the in vivo tests in P. notatum and Poa annua. The seeds were disinfected and inoculated with treatments composed of bacteria and bacteria + F. oxysporum and placed in magenta boxes containing substrate. The seedlings were evaluated for germination rate, root and shoot length, and root and shoot dry weight. Seeds submitted to the same treatments were plated in Petri dishes with 0.7% agarose, and the seedling roots were 3,3’-diaminobenzidine stained and visualized under an optical microscope. In another experiment, 85 nm silica NPs at concentrations of 0.05 mg/mL and 0.1 mg/mL were added to the culture media of Alcaligenes sp., Enterobacter sp., and Serratia sp. A total of 11 treatments were inoculated in disinfected seeds of P. notatum and subjected to the same conditions described previously. Out of 105 isolates, 26 solubilized phosphate, fixed nitrogen, and produced IAA. Serratia sp. and Enterobacter sp. inhibited the C. pupurea growth, but none of them was antagonistic to F. oxysporum. Serratia sp. promoted significant growth of P. notatum. F. oxysporum did not inhibit the development of the seedlings, and promoted the greatest plant growth when inoculated with Enterobacter sp. However, all the seedlings inoculated with F. oxysporum exhibited thin and fragile roots and shoots. The isolates belonging to the genus Pseudomonas promoted significant growth of Poa annua. Bacteria increased the number of root hairs, and it was possible to visualize intracellular bacterial colonization in the roots. In the second experiment, the three bacterial genera without the NPs promoted the growth of P. notatum. Total germination and the highest shoot dry weight were obtained in the treatments of 0.1 mg/mL silica NPs associated with Serratia sp. and Enterobacter sp. Silica NPs associated with the three bacteria increased root length and root dry weight. Bacterial isolates from Paspalum spp. with silica NPs showed potential to be applied as nano-biofertilizers and promote plant growth in P. notatum.